1997
DOI: 10.1164/ajrccm.156.6.9612096
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Immunostimulating Agent on Acute Exacerbations and Hospitalizations in Patients with Chronic Obstructive Pulmonary Disease

Abstract: The PARI-IS Study is a double-blind placebo-controlled randomized clinical trial to study the effect of an immunostimulating agent to prevent acute respiratory exacerbation in patients with COPD. Three hundred eighty-one ambulatory patients (190 placebo and 191 immunostimulant) were followed at home for 6 mo by experienced research nurses. The risk of having at least one episode of acute exacerbation (primary outcome) was similar in the two groups (p = 0.872). In contrast, the total number of days of hospitali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
80
0
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(83 citation statements)
references
References 13 publications
1
80
0
2
Order By: Relevance
“…COPD patients often require emergency and hospital admissions [7,8], which are the largest contributors to healthcare costs [9]. The Obstructive Lung Disease in Northern Sweden (OLIN) studies showed that hospitalisation costs account for .65% of all COPD costs and up to 90% of the diseaserelated expenses of those with more severe disease [9].…”
mentioning
confidence: 99%
“…COPD patients often require emergency and hospital admissions [7,8], which are the largest contributors to healthcare costs [9]. The Obstructive Lung Disease in Northern Sweden (OLIN) studies showed that hospitalisation costs account for .65% of all COPD costs and up to 90% of the diseaserelated expenses of those with more severe disease [9].…”
mentioning
confidence: 99%
“…We have utilized an oral bacterial extract (Broncho-Vaxom OM-85) derived from a mixture of heat-killed respiratory pathogens, which has previously been used in a number of clinical and experimental settings. These include studies of immunostimulation in normal adult experimental animals (7,8) and double-blind multicenter clinical trials with humans with chronic obstructive pulmonary disease (12,30). The principal end points employed for the present study are production of immunoglobulin G1 (IgG1) and IgG2b subclass antibodies, which in the rat are respectively dependent upon Th2 versus Th1 cytokines (14,36).…”
mentioning
confidence: 99%
“…OM-85 BV, which works through mucosa-associated tissue, activates and regulates various components of the immune system. Several randomized clinical trials [10][11][12][13] have shown that OM-85 BV can reduce the number of acute respiratory tract infections (RTIs) by 25% to 50% compared with placebo in adults and children with a history of recurrence.…”
Section: Introductionmentioning
confidence: 99%